2020
DOI: 10.1080/14634988.2020.1816078
|View full text |Cite
|
Sign up to set email alerts
|

Comparative acute toxicity of organophosphates and synthetic pyrethroid pesticides in vivo exposed fresh water fish Oreochromis niloticus (Linnaeus, 1758)

Abstract: Escalating pesticide deposition in the aquatic environment is becoming a potential threat to aquatic organisms. Present study was designed to investigate acute toxicity in O. niloticus. the fish were exposed to five different concentrations of malathion, chlorpyrifos and lambda-cyhalothrin (synthetic pyrethroid) pesticides in the laboratory using separate aquaria for each chemical. Mortality ranged from 100 to 0%. The 24 h LC50 (median lethal concentration) for O. niloticus was 5.70, 0.5 and 0.015 ppm for mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…The treatments and codes were shown in Table 1. glutamic pyruvate transaminase (GPT) and glutamate oxaloacetate transaminase (GOT) [30] were measured on 30th, 60th, 90th, and 120th days after inoculation. Chlorophyll content was determined using a portable chlorophyll analyser (SPAD 502).…”
Section: Pot Experimentsmentioning
confidence: 99%
“…The treatments and codes were shown in Table 1. glutamic pyruvate transaminase (GPT) and glutamate oxaloacetate transaminase (GOT) [30] were measured on 30th, 60th, 90th, and 120th days after inoculation. Chlorophyll content was determined using a portable chlorophyll analyser (SPAD 502).…”
Section: Pot Experimentsmentioning
confidence: 99%
“…These studies have shown that microplastics accumulate and distribute in the gastrointestinal tract, gills, and fish muscles. Ingestion of microplastics in marine animals has been linked to alterations in gastrointestinal tract physiology, immune system depression, oxidative stress, cytotoxicity, differential gene expression, and growth inhibition (Oliviero et al 2019 ; Meaza et al, 2021 ; Kedzierski et al 2018 ; Nabi et al 2019 ; Amin et al 2020 ; Ugwu et al 2021 ). These findings are confirmed by Danopoulos et al ( 2021 ), who reported on the biological endpoint caused by microplastics to different human cells.…”
Section: Toxicological Profiles Of Microplastic Exposurementioning
confidence: 99%
“…For biochemical evaluation 10 fish were transferred to each aquarium (25 × 25 × 25 cm dimension) containing 10 L (liter) of water. Fish were treated for 24 and 48 h with LC 0 doses of malathion (1.425 ppm), chlorpyrifos (0.125 ppm) and λ-cyhalothrin (0.0039 ppm) (Amin et al, 2020). Separate aquarium was used for each pesticide along with three control groups (water without the addition of pesticides).…”
Section: Pesticides Toxicity Testmentioning
confidence: 99%